94.4k views
8 votes
Y=x+1 x-y=1 solve by substitution

User Gisol
by
4.7k points

2 Answers

3 votes

Answer:

no possible answer.

Explanation:

1. y = x+1

2. x-y = 1

3. x = 1+y

Substitute equation 3 into the x in equation 1:

y = (1+y)+1

y = 2+y

y-y = 2

0=2

"0 = 2" isn't valid, thus there is no possible answer to this question.

User Shlomi Borovitz
by
4.7k points
9 votes

Answer:

No Solution

Explanation:

You can use the expression for y provided by the first equation to substitute for y in the second equation.

y = x +1

x -(x +1) = 1

-1 = 1

There are no values of the variables x and y that will make this equation true. The system has No Solution.

__

Additional comment

Solving the second equation for y gives ...

y = x -1

This graphs as a line parallel to the line representing the first equation. A system describing parallel lines has no solution, because the lines never meet, and the solution is the point where they meet.

User Cmpickle
by
5.5k points